Structural fluctuations and aging processes in deeply frozen proteins - Schlichter, J.; Ponkratov, V.V.; Friedrich, J. (Физика низких температур, 2003)
Frozen proteins are nonergodic systems and are subject to two types of structural motions, namely relaxation and fluctuation. Relaxation manifests itself in aging processes which slow the fluctuations. Within certain approximations we are able to experimentally separate the aging dynamics from the fluctuation dynamics by introducing two time parameters, namely an aging time ta and a waiting time tw. Both processes follow power laws in time. The fluctuation dynamics shows features of universality characterized by a rather uniform exponent of 1/4. This universality features were shown to be possible due to a random walk on a 1D random trajectory in conformational phase space. A very interesting aspect of protein dynamics concerns the influence of the host solvent on structural motions of the protein cores. We present results for sugar solvents and discuss possible mechanisms.